Effectiveness and cost-effectiveness of salicylic acid and cryotherapy for cutaneous warts: an economic decision model - Thomas, K.S.; Keogh-Brown, M.R.; Chalmers, J.R.; Fordham, R.J.; Holland, R.C.; Armstrong, S.J.; Bachmann, M.O.; Howe, A.H.; Rodgers, S.; Avery, Anthony; Harvey, I.; Williams, H.C. (NHS R&D HTA Programme, 2006)
Objectives: To estimate the costs of commonly used treatments for cutaneous warts, as well as their health benefits and risk. To create an economic decision model to evaluate the cost-effectiveness of these treatments, and, as a result, assess whether a randomised controlled trial (RCT) would be feasible and cost-effective. Data sources: Focus groups, structured interviews and observation of practice. Postal survey sent to 723 patients. A recently updated Cochrane systematic review and published cost and prescribing data. Review methods: Primary and secondary data collection methods were used to inform the development of an economic decision model. Data from the postal survey provided estimates of the effectiveness of wart treatments in a primary care setting. These estimates were compared with outcomes reported in the Cochrane review of wart treatment, which were largely obtained from RCTs conducted in secondary care. A decision model was developed including a variety of over-the-counter (OTC) and GPprescribed treatments. The model simulated 10,000 patients and adopted a societal perspective. Results: OTC treatments were used by a substantial number of patients (57%) before attending the GP surgery. By far the most commonly used OTC preparation was salicylic acid (SA). The results of the economic model suggested that of the treatments prescribed by a GP, the most cost-effective treatment was SA, with an incremental cost-effectiveness ratio (ICER) of 2.20 £/% cured. The ICERs for cryotherapy varied widely (from 1.95 to 7.06 £/% cured) depending on the frequency of applications and the mode of delivery. The most cost-effective mode of delivery was through nurse-led cryotherapy clinics (ICER = 1.95 £/% cured) and this could be a cost-effective alternative to GP-prescribed SA. Overall, the OTC therapies were the most cost-effective treatment options. ICERs ranged from 0.22 £/% cured for OTC duct tape and 0.76 £/% cured for OTC cryotherapy to 1.12 £/% cured for OTC SA. However, evidence in support of OTC duct tape and OTC cryotherapy is very limited. Side-effects were commonly reported for both SA and cryotherapy, particularly a burning sensation, pain and blistering. Conclusions: Cryotherapy delivered by a doctor is an expensive option for the treatment of warts in primary care. Alternative options such as GP-prescribed SA and nurse-led cryotherapy clinics provide more costeffective alternatives, but are still expensive compared with self-treatment. Given the minor nature of most cutaneous warts, coupled with the fact that the majority spontaneously resolve in time, it may be concluded that a shift towards self-treatment is warranted. Although both duct tape and OTC cryotherapy appear promising new self-treatment options from both a cost and an effectiveness perspective, more research is required to confirm the efficacy of these two methods of wart treatment. If these treatments are shown to be as cost-effective as or more cost-effective than conventional treatments, then a shift in service delivery away from primary care towards more OTC treatment is likely. A public awareness campaign would be useful to educate patients about the self-limiting nature of warts and the possible alternative OTC treatment options available. Two future RCTs are recommended for consideration: a trial of SA compared with nurse-led cryotherapy in primary care, and a trial of home treatments. Greater understanding of the efficacy of these home treatments will give doctors a wider choice of treatment options, and may help to reduce the overall demand for cryotherapy in primary care.